Supply of urban centers with energy resources and the need to preserve the environment case of coal consumption at Baco-Djicoroni - Maiga, Fatoumata; Traore, Ibrahima; Traore, Hamadoun (International Journal of Environment, Agriculture and Biotechnology, 2023)
In Mali, with strong population growth, forest resources are under multiple pressures, the most important of which are agricultural clearing, land speculation and the consumption of wood and/or charcoal as energy fuel. Studies have shown that this is a major problem. According to the FAO (2020, p 21), its production from 2010 to 2018 increased from 137,907 to 379,124 tons against 79,221 Qm to 334,454 Qm between 2008-2017 (MEADD, 2018, pp 41 and 73). The objective aims to demonstrate the challenges of charcoal consumption as fuel in the Baco-Djicoroni district of the Bamako district in order to raise the awareness of decision-makers. The sampling involved 190 people (160 randomly selected households, 24 traders/wholesalers and 6 technical service agents). The methodology was based on the exploitation of documents, the field survey and the analysis and processing of data using Word, Excel and SPSS software. The analysis of the results records 12 charcoal sales depot sites in Baco-Djicoroni with a sales capacity of 7750 bags per week whose households of 10 to 14 people are the biggest consumers, us 89 bags per month. In a context of climate change and forest preservation, the development of a strategy is necessary and alternatives to charcoal remains the promotion of renewable and/or alternative energies.